What your sixth grader needs to know : fundamentals of a good sixth-grade education - Hirsch, E. D. Jr. (Eric Donald), 1928- (Core knowledge series., 2006)
What should your child learn in the sixth grade? How can you help him or her at home? This book answers these important questions and more, offering the specific shared knowledge that thousands of parents and teachers across the nation have agreed upon for American sixth graders.